Process simulation for removing impurities from wastewater using sour water 2-strippers system via Aspen Hysys - Nabgan, B. (Walter de Gruyter GmbH, 2016)
In this paper, Aspen Hysys v8.8 was used to simulate two strippers for sour water stripping process as the aim for removal of chemical impurities such as hydrogen sulfide, carbon dioxide and ammonia in wastewater. As a result of elimination of these impurities, the water can be reused. Comparison between single and two strippers and elevating the stripping efficiency was the objectives of the present study. The feed flow rate and compositions were specified according to the typical Chevron WWT process conditions. The simulation result shows that 100% ammonia was stripped into the two stripper system but only 24% stripped in the single stripper system. The result of H2O was almost same in both systems. The stripped water collected via the bottom of the Ammonia Stripper contains less than 10 ppm of hydrogen sulphide and less than 50 ppm of ammonia.